FORMULASI KRIM EKSTRAK KULIT PISANG AGUNG SEMERU DAN PISANG MAS KIRANA VARIETAS LUMAJANG - Dwi Nur Rikhma Sari; David Kristian Susilo; Siti Zainiyatus Zakiyah; Washila Khoiriyah; Siti Nur Kholifah (Biota, 2018)
Banan peel of Agung Semeru and banana peel of Mas Kirana, is one part of banana fruit containing antimicrobial compounds that contain phytochemical components. The purpose of this research is to know the quality of cream from banana peel extract of Agung Semeru, Mas Kirana and combination of both using 100% concentration (the best concentration, based on previous research results). In the test the cream is done organoleptic test, test homogeneity, spreading test, pH test and absorption test. The results obtained on the organoleptic test seen from the color of brown cream, semi-solid dosage form, and the smell of banana skin cream typical test homogeneity does not occur agglomeration, pH ranges from 5-6 and still safe for the skin, has a cream that meets the requirements of absorption that is more 1 mg / 1 ml. A / M cream scattering test is easy to be applied so that the extract cream of skin extract of Agung Semeru banana skin extract, Mas Kirana and combination fulfill the scatter test.